2008
DOI: 10.1590/s0100-54052008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade patogênica e efeito de carboidratos no crescimento micelial, esporulação e agressividade de Colletotrichum gloeosporioides da pupunheira

Abstract: A agressividade de 17 isolados de Colletotrichum gloeosporioides associados à antracnose em folhas da pupunheira (Bactris gasipaes), oriundos de estados no Norte, Sudeste e Sul do Brasil, foi avaliada através de bioensaio com folhas de pupunheira destacadas, em três estágios de desenvolvimento: jovem, intermediária e completamente expandida. Diferenças significativas na agressividade dos isolados foram verificadas apenas em folhas completamente expandidas e intermediárias. O emprego de diferentes carboidratos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
3
0
3
Order By: Relevance
“…The ability of M. perniciosa to degrade starch was previously reported (Bastos 2005) for Alternaria solani (Marchi et al 2006) and Uromyces phaseoli (Wang 1961) and changes in starch content following infection were reported for cacao infected by M. perniciosa (Scarpari et al 2005;Sreenivasan and Dabydeen 1989). The association of starch (carbon) and aggressiveness was demonstrated by Mafacioli et al (2008), who showed that anthracnose (Colletotrichum gloeosporioides) on leaves of peach palm (Bactris gasipaes) increased when conidia were produced on potato-agar medium supplemented with starch. Similarly, Assis et al (2001) observed that growth of C. gloeosporioides isolates in starch-enriched medium favored pathogenicity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The ability of M. perniciosa to degrade starch was previously reported (Bastos 2005) for Alternaria solani (Marchi et al 2006) and Uromyces phaseoli (Wang 1961) and changes in starch content following infection were reported for cacao infected by M. perniciosa (Scarpari et al 2005;Sreenivasan and Dabydeen 1989). The association of starch (carbon) and aggressiveness was demonstrated by Mafacioli et al (2008), who showed that anthracnose (Colletotrichum gloeosporioides) on leaves of peach palm (Bactris gasipaes) increased when conidia were produced on potato-agar medium supplemented with starch. Similarly, Assis et al (2001) observed that growth of C. gloeosporioides isolates in starch-enriched medium favored pathogenicity.…”
Section: Discussionmentioning
confidence: 88%
“…Changes in starch and amylase content following infection have been reported in many plant-pathogen interactions; i.e. peach palm x anthracnose (Colletotrichum gloeosporioides; Mafacioli et al 2008), mulberry x yellow mulberry dwarf (Phytoplasma; Gai et al 2014), arabidopsis x white blister rust (Albugo candida; Chou et al 1995), rice x rice blast (Magnaporthe oryzae; Badaruddin et al 2013) and cacao x witches' broom disease (M. perniciosa; Scarpari et al 2005;Sena et al 2014). The general temporal pattern in starch production is an initial decrease followed by a marked increase around the infection site.…”
Section: Section Editor: Jorge Teodoro De Souzamentioning
confidence: 99%
“…Colletotrichum são decorrentes do fator genotípico cuja expressão fenotípica, decorrente da biossíntese de enzimas e metabólitos específicos mediante estímulo de substratos particulares, permite variações culturais e de severidade ( SUTTON, 1992;LÓPEZ, 1999;MAFACIOLI et al, 2006MAFACIOLI et al, , 2008 …”
Section: As Diferenças Morfoculturais De Espécies Deunclassified
“…Esse é um fungo mitospórico, ordem Melanconiales, Classe Coelomycetes; na sua fase teleomórfica, está associado com estirpes homotálicas ou heterotálicas de Glomerella cingulata (filo Ascomycota, ordem Phyllachorales) (SUTTON, 1992;ALEXOPOULOS et al, 1996;KENDRICK, 2001). A antracnose é a principal doença que vem causando danos principalmente em mudas na fase de viveiro e em plantios adultos (ALVES; BATISTA, 1981;SANTOS et al, 2000;SANTOS et al, 2001a;MAFACIOLI et al, 2003;. A enfermidade tem sido diagnosticada tanto nas regiões onde a planta é nativa como naquelas em que foi introduzida .…”
Section: Doenças Da Parte Aérea Antracnoseunclassified
“…Em estágio mais avançado de colonização, as manchas tornam-se enegrecidas, com coloração negra intensa, devido ao desenvolvimento de outros fungos saprófitas . Todos os sintomas foram observados em plantas naturalmente infectadas, em plantas nativas e diferentes campos de produção dos estados do Amazonas (ALVES; BATISTA, 1981;1983;MOTA et al, 1993), São Paulo (PIZZINATTO et al, 1996), Pará (POLTRONIERI et al, 1999, Paraná (SANTOS et al, 2000;2001) e Minas Gerais (VIDA et al, 2003).…”
Section: Doenças Da Parte Aérea Antracnoseunclassified